2020
DOI: 10.1002/pc.25681
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cellulosic fillers on the mechanical, morphological, thermal, viscoelastic, and rheological properties of polyhydroxybutyrate biopolymers

Abstract: The aim of this study was to determine the effects of cellulosic fillers on the conventional and dynamic mechanical, thermal, morphological, and rheological properties of polyhydroxybutyrate (PHB) biopolymers. Polyhydroxybutyrate as a biopolymer matrix and cellulosic fillers including wood flour, microcrystalline cellulose, and cellulose nanofibrils (0.5 and 5 wt%) as reinforcing agents were used to produce the composite. According to the results obtained, the addition of 0.5 wt% cellulose nanofibrils improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
(74 reference statements)
1
15
0
Order By: Relevance
“…The neat polymeric matrices showed a degradation profile with one major weight loss at 236 • C and 281 • C for PHB P209E and PHB P226, respectively, and 336 • C and 364 • C for PLA 3D860 and PLA 3100HP, respectively. These main weight losses, credited to the degradation of the polymeric backbone, are in agreement with the maximum degradation temperatures of other PHB [62,63] and PLA [34,64] grades reported in the literature. Apart from PLA 3100HP, the other matrices showed a small degradation step at 338 • C, 395 • C, and 456 • C for PHB P209E, PHB P226, and PLA 3D860, respectively, which were likely due to the degradation of the additives.…”
Section: Thermal Analysissupporting
confidence: 90%
“…The neat polymeric matrices showed a degradation profile with one major weight loss at 236 • C and 281 • C for PHB P209E and PHB P226, respectively, and 336 • C and 364 • C for PLA 3D860 and PLA 3100HP, respectively. These main weight losses, credited to the degradation of the polymeric backbone, are in agreement with the maximum degradation temperatures of other PHB [62,63] and PLA [34,64] grades reported in the literature. Apart from PLA 3100HP, the other matrices showed a small degradation step at 338 • C, 395 • C, and 456 • C for PHB P209E, PHB P226, and PLA 3D860, respectively, which were likely due to the degradation of the additives.…”
Section: Thermal Analysissupporting
confidence: 90%
“…The applicability of natural fibers such as hemp and flax as a reinforcement material was addressed by Loos et al [ 102 ], and the mechanical characteristics of flax and hemp employed in polymer reinforcement were studied. Previously, researchers showed that adding natural fibers to PLA bio composites improves their flexural, tensile, and impact strength [ 103 , 104 , 105 , 106 , 107 ].…”
Section: Polylactic Acid (Pla)mentioning
confidence: 99%
“…In contrast, viscoelastic properties such as the storage modulus, loss modulus and the damping properties (tan δ) are rarely reported. For applications of commercial PHB, detailed characterizations of PHB composites with cellulose fibers have been reported, 15,16 which can be used in food packaging. 17 PHB synthesized from glucose or vegetable oils have a high degree of crystallinity ranging from 60% to 80%.…”
Section: Introductionmentioning
confidence: 99%